Experimental investigation of thermophysical properties and heat transfer rate of covalently functionalized MWCNT in an annular heat exchanger - Arzani, H.K.; Amiri, A.; Kazi, S.N.; Chew, B.T.; Badarudin, A. (Elsevier, 2016)
In a novel direct amidation, multi-walled carbon nanotubes (MWCNT) is covalently functionalized with aspartic acid (Asp) to achieve a highly dispersed colloidal suspension including MWCNT. After investigation of colloidal stability of functionalized MWCNT with Asp (MWCNT-Asp) in aqueous media by UV-Vis spectroscopy, less than 20% sediment was occurred for highest weight concentration of 0.1%. The prepared coolants had some promising properties such as high thermal conductivity as compared with base fluid. Also, thermophyisical properties were investigated to check its suitability. The prepared water-based coolants with different weight fractions of MWCNT-Asp were experimentally investigated in terms of heat transfer rate in a horizontal annular heat exchanger. Forced convection heat transfer coefficient and pressure drop were investigated in transition and turbulent regimes for three different heat fluxes and four weight fractions. Annular heat exchanger showed a significant increase in heat transfer rate. Also poor change in the pressure drop in the presence of different weight concentrations provides a suitable condition for this novel alternative coolant. Also, insignificant increase in pumping power was obtained, which shows its suitability for industrial applications.